The faiths of others : a history of interreligious dialogue - Howard, Thomas Albert, 1967- (New Haven Yale University, 2021)
The first intellectual history of interreligious dialogue, a relatively new and significant dimension of human religiosity.
Harbingers -- Chicago -- London -- Rome.
Includes bibliographical references and index.
Keywords: Religions -- Relations; Christianity and other religions; Religious pluralism -- History; Christianity and other religions; Interfaith relations; Religions; Religious pluralism; History